Autofluorescence in eleocytes of some earthworm species. - Barbara Płytycz; A John Morgan; Stephen R StĂźrzenbaum; Michael O' Reilly; Graham P Feeney; Justyna Cholewa (Folia Histochemica et Cytobiologica, 2006)
Immunocompetent cells of earthworms, coelomocytes, comprise adherent amoebocytes and granular eleocytes (chloragocytes). Both cell populations can be expelled via dorsal pores of adult earthworms by exposure to an electric current (4.5 V) for 1 min. Analysis by phase contrast/fluorescence microscopy and flow cytometry demonstrated that eleocyte population of several species exhibits a strong autofluorescence. A high percentage (11-35%) of autofluorescent eleocytes was recorded in Allolobophora chlorotica, Dendrodrilus rubidus, Eisenia fetida, and Octolasion sp. (O. cyaneum, O. tyrtaeum tyrtaeum and O. tyrtaeum lacteum). In contrast, autofluorescent coelomocytes were exceptionally scarce (less than 1%) in representative Aporrectodea sp. (A. caliginosa and A. longa) and Lumbricus sp. (L. castaneus, L. festivus, L. rubellus, L. terrestris). Thus, this paper for the first time describes profound intrinsic fluorescence of eleocytes in some--but not all--earthworm species. The function (if any) and inter-species differences of the autofluorescent coelomocytes still remain elusive.